2020
DOI: 10.1111/ctr.14165
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation of supraventricular arrhythmias after orthotopic heart transplantation: Long‐term follow‐up of a single‐center experience

Abstract: Background Supraventricular arrhythmias (SVAs), commonly managed with radiofrequency ablation (RFA), may occur after orthotopic heart transplantation (OHT). Methods We retrospectively assessed 514 consecutive patients (pts.) undergoing OHT between January 1990 and July 2016 in a single‐center. Patients with SVAs managed with RFA were included. Mechanisms of genesis of SVAs, association with surgical techniques and outcomes, were analyzed. Results Of 514 pts undergoing OHT, 53% (272 pts.) were managed with bica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Clinical management of HTX recipients with late-onset post-transplant AFL involves electrical cardioversion, pharmacological cardioversion, catheter ablation, and in some cases conservative treatment due to spontaneous conversion of AFL [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Initial standard treatment of patients with new-onset AFL after HTX predominantly consists of electrical or pharmacological cardioversion [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical management of HTX recipients with late-onset post-transplant AFL involves electrical cardioversion, pharmacological cardioversion, catheter ablation, and in some cases conservative treatment due to spontaneous conversion of AFL [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Initial standard treatment of patients with new-onset AFL after HTX predominantly consists of electrical or pharmacological cardioversion [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the last two decades, treatment and clinical management of HTX recipients with late-onset post-transplant AFL has changed towards a more invasive approach focusing on radiofrequency catheter ablation with three-dimensional electroanatomical mapping systems in order to better understand the underlying mechanisms of post-transplant AFL [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Taylor and colleagues [ 25 ] reported that they treated post-transplant AFL with electrical or pharmacological cardioversion prior to 2002 and started performing catheter ablation for post-transplant AFL hereafter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49,50 Although less common, SVT may occur in stable OHT patients secondary to atrial flutter and reentry tachycardia due to the proarrhythmic effects of surgical scars. 51,52 Historically, the use of adenosine has been considered a relative contraindication in OHT patients by many experts due to the increased sensitivity of the SA and AV node to sympathomimetic amines secondary to parasympathetic denervation, thus increasing the risk for prolonged AV block. 53 This effect has been demonstrated in clinical studies and has shown a 3-to 5-fold greater response to adenosine.…”
Section: Heart Transplant Recipientsmentioning
confidence: 99%
“…49,50 Although less common, SVT may occur in stable OHT patients secondary to atrial flutter and reentry tachycardia due to the proarrhythmic effects of surgical scars. 51,52…”
Section: Special Populationsmentioning
confidence: 99%